Return to Our Times: Juozas Aputis’s Relevance “Then” and “Now” - Kalėda, Algis (Colloquia, 2018)
The author of this article uses narratological and semiotic analysis to conduct a new reading of Juozas Aputis’s classic stories, while at the same time engaging in a dialogue with interpreters who have used different methodologies. Having established that Aputis writes about fundamental existential matters, the author of the article discusses how his texts communicate experiences that cannot be contained by empirical reality – the unconscious reservoirs within human beings that occasionally distort our behavior and feelings. According to the narrated events, the narrator is not only an observer of action but also an engaged participant in it and one who always remains empathic toward oppressed characters and the world at large. This kind of empathy is further developed in the works of twentieth century Lithuanian prose classic Jonas Biliūnas. The author of the article argues that readers’ understanding of Aputis’s prose oscillates between the model of prose that promotes traditional rural values and more universal dimensions of expression.
Keywords: Lithuanian pros; Juozas Aputis; short story; late Soviet period; parable